THE RELATION BETWEEN STUDENTS’ IT VOCABULARY MASTERY AND THE STUDENTS’ ACHIEVEMENT OF ENGLISH I AT AMIK CIPTA DARMA SURAKARTA - Nurhidayanto Nurhidayanto (Jurnal Ilmiah IT CIDA: Diseminasi Teknologi Informasi, 2015)
This research was aimed at investigating the relation between AMIK Cipta Darma Surakarta students’ IT vocabulary mastery and their final achievement of English I –to find whether or not they have linear or opposite relation. This research was a correlational-descriptive one. It was descriptive for it tried to get a detailed description about related facts of students’ IT vocabulary mastery (X) and of English I learning achievement (Y); and it was correlational since it detected how closed the dependent variable to the independent variable. This research approach was quantitative i.e. the numeric data of the 149 population students (at 5% df) were statistically analyzed –to analyze whether or not the students’ IT vocabulary mastery (X) influenced the students’ English I learning achievement (Y). In addition, some cases that violated from the research hypothesis (taken from open/close ended interview) were qualitatively analyzed. The analysis done yielded 1) that the students’ IT vocabulary mastery (X) had relation to students’ English I learning achievement (Y) as seen at the value of rcalculation > rtable (0,68 > 0,176) with p value < α (0,000 < 0,05); 2) that the regression equation was Y = 30,71 + 0,62X –meaning that if the variable of students’ IT vocabulary mastery had a constant value, the students’ achievement of English I would increase 30,71; and 3) that every increasement   on the students’ IT vocabulary mastery (X) would increase the value of students’ English I learning achievement (Y) in 0,62. In practise, when the student has a score of 50 in the IT vocabulary test, s/he will achive 61,71 in her/his English I Achievement. Key words: Information Technolog, Learning Achievement, Vocabulary Mastery